Mammal Biochronology (Land Mammal Ages) Around the World From Late Miocene to Middle Pleistocene and Major Events in Horse Evolutionary History - Rook, Lorenzo; Bernor, Raymond L.; Avilla, Leonardo S.; Cirilli, Omar; Flynn, Lawrence; Jukar, Advait; Sanders, William; Scott, Eric; Wang, Xiaoming (Frontiers in Ecology and Evolution, 2019)
Biochronology is important to vertebrate chronology because the primary temporal units developed and applied by vertebrate paleontologists for correlation of terrestrial deposits (Land Mammal Ages, LMA) are all biochronologic units. Specific mammal biochronologic scales have been developed for Europe (MN units or ELMA), Asia (ALMA), North America (NALMA) and South America (SALMA). Each timescale is based on land mammal first appearances and characteristic associations on different continental landmasses. Herein, we summarize and review the bases for recognizing mammalian biochronologic units with the most recent update of the Land Mammal Ages. We correlate these ages with the global magnetochronostratigraphic and geochronologic time scales including the major equid evolutionary events of the last 8 million years.